The future of hospital quality of care policy: A multi-stakeholder discrete choice experiment in Flanders, Belgium. Issue 12 (December 2021) - Brouwers, Jonas; Cox, Bianca; Van Wilder, Astrid; Claessens, Fien; Bruyneel, Luk; De Ridder, Dirk; Eeckloo, Kristof; Vanhaecht, Kris
Highlights: DCEs are a promising way to involve stakeholders in healthcare policy setting. Attitudes on quality initiatives differ among healthcare workers, patient representatives and policymakers. Quality of care policy should be tailored to the local healthcare context. Healthcare quality initiatives should be developed bottom-up with input from stakeholders. External quality control and public transparency remain essential in future quality policy. Abstract: Background: Collaboration between policymakers, patients and healthcare workers in hospital quality of care policy setting can improve the integration of new initiatives. The aim of this study was to quantify preferences for various characteristics of a future quality policy in a broad group of stakeholders. Materials and methods: 450 policymakers, clinicians, nurses, patient representatives and hospital board members in Flanders (Belgium) participated in five discrete choice experiments (DCE) on quality control, quality improvement, inspection, patient incidents and transparency. For each DCE, various attributes and levels were defined from a literature review and interviews with 12 international quality and patient safety experts. Results: For the attributes with the highest relative importance, participants exhibited a strong preference for quality control by an independent national organization and coordination of quality improvement initiatives at the level of hospital networks. The individual hospital was chosen over the government for setting up an action plan following patient complaints. Respondents also strongly preferred mandatory reporting of severe patient incidents and transparency by publicly reporting quality indicators at the hospital level. Conclusions: A future quality model should focus on a multicomponent approach with external quality control, improvement actions on hospital network level and public transparency. DCEs provide an opportunity to incorporate the attitudes and views for individual components of a new policy recommendation.